Using GIS, remote sensing, and machine learning to highlight the correlation between the land-use/land-cover changes and flash-flood potential - Costache R.; Pham Q.B.; Corodescu-Ro?ca E.; Cmpianu C.; Hong H.; Thuy Linh N.T.; Fai C.M.; Ahmed A.N.; Vojtek M.; Pandhiani S.M.; Minea G.; Ciobotaru N.; et al. (MDPI AG, 2023)
Catchments; Climate change; Earth (planet); Floods; Image processing; Land use; Machine learning; Multilayer neural networks; Remote sensing; Runoff; Geographically weighted regression; Land use/land cover change; Machine learning techniques; Meteorological phenomena; Multilayer perceptron neural networks; Pearson coefficient; Runoff potentials; Synthetic dynamics; Geographic information systems